Determinants of earnings management in the hotel industry: an international perspective - Paiva, I.; Lourenço, I. (Corporate Ownership And Control, 2016)
This paper analyzes the determinants of the level of earnings management in a wide sample of listed firms from the hotel industry in 15 countries. The empirical study relies on the discretionary accruals, as an indication of earnings management, and examines the firm and country characteristics that are potentially associated with those discretionary accruals. The results suggest that firm characteristics, including the leverage ratio, cash flow from operations, investment opportunities and the frequency of losses, are the major determinant of earnings management in the hotel industry around the world. Our results also show that firms with five star hotels have different incentives to manipulate earnings, when compared to firms holding lower quality hotels. The hotels’ star rating also seems to play a different role in explaining the level of earnings management in common-law countries, when compared to code-law countries. This paper contributes to the accounting literature by examining the determinants of earnings management of a large panel of firms from the hotel industry and by focusing on the characteristics of the firm and its institutional environment.